2006
DOI: 10.1007/s00348-006-0219-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact pressures of turbulent high-velocity jets plunging in pools with flat bottom

Abstract: Dynamic pressures created by the impact of high-velocity turbulent jets plunging in a water pool with flat bottom were investigated. Pressure fluctuations were sampled at 1 kHz at the jet outlet and at the pool bottom using piezo-resistive pressure transducers, jet velocities of up to 30 m/s and pool depth to jet diameter ratios from 2.8 to 11.4. The high-velocity jets entrain air in the pool in conditions similar to prototype applications at water release structures of dams. The intermittent character of plun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 12 publications
6
16
0
Order By: Relevance
“…In the confinedbottom case, the deeper the pool, the more the pressure fluctuations were reduced. For the flat-bottom case, C' p values were higher for the deep pool (Y/d j = 11.1), in agreement with Bollaert and Schleiss (2005) and Manso et al (2007), who found that a developed jet impact on the bottom produces higher pressure fluctuations than a core jet.…”
Section: Influence Of Pool Confinement and Jet Aerationsupporting
confidence: 81%
See 1 more Smart Citation
“…In the confinedbottom case, the deeper the pool, the more the pressure fluctuations were reduced. For the flat-bottom case, C' p values were higher for the deep pool (Y/d j = 11.1), in agreement with Bollaert and Schleiss (2005) and Manso et al (2007), who found that a developed jet impact on the bottom produces higher pressure fluctuations than a core jet.…”
Section: Influence Of Pool Confinement and Jet Aerationsupporting
confidence: 81%
“…To evaluate the dynamic pressures acting on a rock mass, a solid but fissured media has to be considered instead of loose sediments. Systematic experiments using high-velocity jets in a large facility were performed by Bollaert and Schleiss (2003b), Manso et al (2007), Federspiel (2011), and Duarte et al (2015 for pools with a flat bottom and by Manso (2006) and Manso et al (2009) for confined pool bottoms. These researches conducted in the Laboratory of Hydraulic Constructions (LCH) of the Ecole Polytechnique Fédérale de Lausanne (EPFL) developed a physically-based description of rock scour.…”
Section: Introductionmentioning
confidence: 99%
“…Ervine et al (1997) mention that jet diffusion in the plunge pool is furthermore relevant for limited pressure fluctuations on the pool bottom, and that air entrained by the jet reduces bottom pressure amplitudes. Manso et al (2007) show that dynamic pressures at the bottom of shallow and deep pools often follow a Gaussian distribution.…”
Section: Introductionmentioning
confidence: 98%
“…Ervine and Falvey (1997) studied the behavior of water jets plunging through the atmosphere, analyzing the physical properties of the jets and their spreading. Furthermore, Manso et al (2007) conducted a comprehensive analysis on the dynamic pressures at the issuance and at the bottom of the pool investigating velocities and aeration conditions similar to those occurring in prototypes.…”
Section: Introductionmentioning
confidence: 99%